Georgia : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
This report is based on the progress of the Economic Development and Poverty Reduction Program (EDPRP) in Georgia. It highlights the status of measures intended for rapid and sustainable economic development in the country through further fine-tuning of administrative mechanisms, increase of transparency, improvement of the business climate, and liberalization of the economy. It explains the ongoing and planed reforms in the sectoral spectrum and rehabilitation of post-conflict zones. Economic processes have developed positively resulting in acceleration of the economic growth rate in the country.